"The best thing I can do for readers is read!": how one teacher conducts interactive multimodal read-alouds using nonfiction picture books (New Jersey: Wiley Company, 2024)
Nonfiction is more engaging than ever before! See how one kindergarten teacher encourages mutlimodal reader responses through interactive whole-group read-alouds using nonfiction picture books.
Keywords: Picture books